Belatacept treatment for two yr after liver transplantation is not associated with operational tolerance. (10th December 2014) - Schwarz, Christoph; Rasoul‐Rockenschaub, Susanne; Soliman, Thomas; Berlakovich, Gabriela A.; Steininger, Rudolf; Mühlbacher, Ferdinand; Wekerle, Thomas
Abstract Belatacept was recently evaluated in liver transplantation (LT) in a phase II multicenter trial, which was terminated prematurely. Patients were more than two yr post‐LT at the time. As high rates of spontaneous tolerance after LT have been reported and as belatacept has marked immunomodulatory effects, we decided to maintain the belatacept patients enrolled at our center (n = 4) on MMF monotherapy. All belatacept patients on MMF monotherapy developed graft dysfunction consistent with acute rejection after a mean period of 10.3 (7–14) wk. Patients were therefore switched to triple therapy with CNI, MMF, and corticosteroids. Graft dysfunction resolved within 1–3 wk after switch. At the time of belatacept discontinuation, mean eGFR was 105.1 mL/min/1.73 m² (92.1–118.9) in belatacept patients compared to 58 mL/min/1.73 m² (36.1–98.2) in controls (p = 0.022). One yr after the switch to CNI therapy, eGFR had declined by 27.4 mL (19.2–39.3; p = 0.008). Thus, LT patients treated with belatacept show superior kidney function that declines upon institution of CNIs. MMF monotherapy following withdrawal of belatacept is associated with a high incidence of graft dysfunction. Belatacept has no obvious immunomodulatory effects in LT recipients that would be sufficient to allow drug withdrawal with a high rate of success.